Ad

2y - x = 3

x = 3y - 5

Add the two equations side by side,

2y - x + x = 3 + 3y - 5

2y = 3y - 2

y = 2

Plug this in the second equation to get x,

x = 3(2) - 5

x = 1

So the solution is **x = 1**, **y = 2**

or in ordered pair notation **(1, 2)**

Posted on Jun 29, 2009

Ad

'3y+5'-3=0

Posted on Jun 06, 2011

Ad

Hi there,

Save hours of searching online or wasting money on unnecessary repairs by talking to a 6YA Expert who can help you resolve this issue over the phone in a minute or two.

Best thing about this new service is that you are never placed on hold and get to talk to real repairmen in the US.

Here's a link to this great service

Good luck!

Posted on Jan 02, 2017

Mar 26, 2018 | Mitsubishi Pajero Cars & Trucks

To find the solution, first find the value of y for each equation.

Then substitue one equation into the other so that you only the x variable left.

Then just solve for x.

Once you have a value for x, then you can easily solve for y.

So for the first equation:

3y - 6x = -3

3y = 6x - 3

**y = 2x - 1**

Now for the second equation:

2y + 8x = 10

2y = -8x + 10

**y = -4x + 5**

Since both equations equal y, they also equal each other, therefore:

2x - 1 = -4x + 5

Now just solve for x:

2x + 4x = 5 + 1

6x = 6

**x=1**

Now substitute x=1 into either original equation:

y = 2x - 1

y = 2 (1) - 1

y = 2 - 1

**y = 1**

Therefore the solution is x=1 and y=1

Good luck, I hope that helps.

Joe.

Then substitue one equation into the other so that you only the x variable left.

Then just solve for x.

Once you have a value for x, then you can easily solve for y.

So for the first equation:

3y - 6x = -3

3y = 6x - 3

Now for the second equation:

2y + 8x = 10

2y = -8x + 10

2x - 1 = -4x + 5

Now just solve for x:

2x + 4x = 5 + 1

6x = 6

y = 2x - 1

y = 2 (1) - 1

y = 2 - 1

Good luck, I hope that helps.

Joe.

Nov 09, 2011 | Texas Instruments TI-84 Plus Silver...

Todd is 4 years old.

Let Tom's age = X

Let Todd's age = Y

From the given facts:

X = 5Y

and

X + 7 + 6 = 3 ( Y + 7 )

X+13 = 3Y + 21

X = 3Y + 8

So if:

X=5Y

and

X=3Y+8

Then:

5Y=3Y+8

2Y=8

Y=4

I hope that helps.

Joe.

Let Tom's age = X

Let Todd's age = Y

From the given facts:

X = 5Y

and

X + 7 + 6 = 3 ( Y + 7 )

X+13 = 3Y + 21

X = 3Y + 8

So if:

X=5Y

and

X=3Y+8

Then:

5Y=3Y+8

2Y=8

Y=4

I hope that helps.

Joe.

Sep 14, 2011 | Office Equipment & Supplies

Do you really need a calculator to solve a linear equation?

Let us see how to solve it without a calculator.

Remove the parentheses fronm the second term on the left : y-3

Use the distributive property on the last term on the right side -2y-6

Take the term -3 to the right side, changing its sign in the process (becomes +3)

Take the -2y term to the left making it +2y.

3y +2y=18+3-6 or 5y=15 and the answer is straightforward .

As to your Casio FX300ES, it cannot solve equations because it does not have an EQUATION calculation mode. The Casios FX-115ES and FX-991ES have an Equation Mode. If you use any of the two to solve an equation in one variable (linear, quadratic or other) the unknown is taken to be x by default. You would have to change the name of the variable from y to x.

Let us see how to solve it without a calculator.

Remove the parentheses fronm the second term on the left : y-3

Use the distributive property on the last term on the right side -2y-6

Take the term -3 to the right side, changing its sign in the process (becomes +3)

Take the -2y term to the left making it +2y.

3y +2y=18+3-6 or 5y=15 and the answer is straightforward .

As to your Casio FX300ES, it cannot solve equations because it does not have an EQUATION calculation mode. The Casios FX-115ES and FX-991ES have an Equation Mode. If you use any of the two to solve an equation in one variable (linear, quadratic or other) the unknown is taken to be x by default. You would have to change the name of the variable from y to x.

Sep 08, 2011 | Casio fx-300ES Calculator

Price of bag of chips s X and price of box of pretzels is Y.

Now you can write following equations:

2X+3Y=413

X+2Y=239

From second equation you know that X is 239-2Y, and you put that in first equation:

2*(239-2Y)+3Y=413

or

-4Y+3Y=413-2*239

Finally we have for Y: Y=65 and X=239-2Y=109.

Now you can write following equations:

2X+3Y=413

X+2Y=239

From second equation you know that X is 239-2Y, and you put that in first equation:

2*(239-2Y)+3Y=413

or

-4Y+3Y=413-2*239

Finally we have for Y: Y=65 and X=239-2Y=109.

Aug 13, 2011 | Office Equipment & Supplies

You have to put the equations into matrix form first. To do this, each variable has one column in the first matrix and you fill in the co-efficients for the variables. The second matrix has one column and contains all the numbers.

{ 2 -1 1 -1} = Matrix A

{ 1 3 -2 0}

{ 3 -2 0 4}

{-1 -3 -3 -1}

{-1} = Matrix B

{-5}

{ 1}

{-6}

{x=-2} = A*(B^-1)

{y=-.2}

{z=3}

{w=1/6}

I used excel for all my calculation and a helpful tutorial can be found here. I hope this helps and have a nice day!

{ 2 -1 1 -1} = Matrix A

{ 1 3 -2 0}

{ 3 -2 0 4}

{-1 -3 -3 -1}

{-1} = Matrix B

{-5}

{ 1}

{-6}

{x=-2} = A*(B^-1)

{y=-.2}

{z=3}

{w=1/6}

I used excel for all my calculation and a helpful tutorial can be found here. I hope this helps and have a nice day!

May 05, 2011 | Computers & Internet

(2x - 3y)(3x + 2y) = 2x*3x + 2x*2y - 3y*3x - 3y*2y

= 6x^2 + 4xy - 9xy - 6y^2

= 6x^2 - 5xy - 6y^2 You multiply each element in the first set of brackets by each element in the second set of brackets and then consolidate like terms and arrange them in sequence of powers, first x and then y. So:

2x by 3x = 6x squared

2x by 2y = 4xy

-3y by 3x = -9xy

-3y by 2y = 6y squared

6x squared -5xy + 6y squared

= 6x^2 + 4xy - 9xy - 6y^2

= 6x^2 - 5xy - 6y^2 You multiply each element in the first set of brackets by each element in the second set of brackets and then consolidate like terms and arrange them in sequence of powers, first x and then y. So:

2x by 3x = 6x squared

2x by 2y = 4xy

-3y by 3x = -9xy

-3y by 2y = 6y squared

6x squared -5xy + 6y squared

Dec 04, 2010 | Yahoo Computers & Internet

(x+3y=0)*3=3x+9y

y=1 x= -3

y=1 x= -3

Jun 29, 2008 | Bagatrix Algebra Solved! 2005 (105101) for...

B. 2((2-Y)/3)-Y=3

2(2-Y)-Y=9

4-2Y-Y=9

-3Y=9-4

-3Y=5

-Y=5/3

Y=-1.67

A. 3X+(-1.67)=2

3X-1.67=2

3X=2+1.67

3X=3.67

X=3.67/3

X=1.22

2(2-Y)-Y=9

4-2Y-Y=9

-3Y=9-4

-3Y=5

-Y=5/3

Y=-1.67

A. 3X+(-1.67)=2

3X-1.67=2

3X=2+1.67

3X=3.67

X=3.67/3

X=1.22

Nov 05, 2007 | SoftMath Algebrator - Algebra Homework...

Jun 22, 2018 | HP Computers & Internet

812 people viewed this question

Usually answered in minutes!

×